Review of the Role of Digital Technology and Self-Efficacy in Forming Entrepreneurial Intention: Entrepreneurial Behavior of Photo Studio - Amboningtyas, Dheasey; Lestari, Sinta Petri; Haryono, Andi Tri; Restu Febrianto, Aziza (Sean Institute, 2025)
This study examines how self-efficacy and digital technology contribute to the emergence of entrepreneurship among photo studio businesses in Semarang City. This study uses Structural Equation Modeling (SEM) analysis tools to show the positive influence of digital technology on entrepreneurial ambition. Another factor in the decision to launch a business is self-efficacy or confidence in one's skills. Self-efficacy, digital technology, and entrepreneurial ambition are interrelated through entrepreneurial activity. The study shows that digital technology, increased self-efficacy, and entrepreneurial drive are essential elements to improve the welfare of photo studios in the Semarang City environment. Therefore, increasing technical empowerment, strengthening self-confidence, and fostering entrepreneurial behavior are key to increasing the success of photo studios. This study advances knowledge about the critical elements influencing entrepreneurial tendencies in the digital era by explaining the complex interactions between these variables. To increase local economic prosperity and entrepreneurial potential, policies and strategies that support photo studios in Semarang City can be developed using the practical consequences of this study.